Near-ideal compressive strength of nanoporous silver composed of nanowires. (July 2019) - Peng, Peng; Sun, Hao; Gerlich, Adrian P.; Guo, Wei; Zhu, Ying; Liu, Lei; Zou, Guisheng; Singh, Chandra Veer; Zhou, Norman
Abstract: Nanoporous materials exhibit promising applications in energy storage, catalysis, and sensing. They are typically synthesized by dealloying, a costly and environmentally detrimental technology, valid only within a narrow compositional range of alloys. Surmounting these disadvantages, we assembled nanoporous silver materials via bottom-up nanoscale joining of nanowires, a technique also suitable for other metals. Furthermore, the resulting nanoporous materials exhibit an unprecedented, near-ideal compressive yield strength (∼2.6 GPa). Such an ultra-high strength, however, does not belong to the nanoporous materials composed of nanowires with the minimum length in our samples, challenging the smaller-is-stronger tenet. According to molecular dynamics simulations, such a strength degradation as nanowires shorten is attributed to the internal compressive stress arising from the five-fold twins within nanowires. Such internal stress maximizes at the center and diminishes near free surfaces, making the center part harder to compress than that adjacent to the free surfaces. The volume fraction of the latter increases as the nanowire shortens, diminishing the overall Young's modulus. For nanowires having aspect ratios smaller than six, a reduced Young's modulus lowers the yield strength since the yield strain is independent of aspect ratios. However, if the aspect ratio exceeds six, compression induces bending, reducing both yield strength and yield strain. Overall, this work not only provides new physical insights on the structure-mechanical property relationship for nanoporous silver, but also paves a new way for bottom-up synthesizing nanoporous metals with ultra-high compressive strength efficiently, economically, and environmental-friendly. Graphical abstract: Image 1